The inflated mitochondrial genomes of siphonous green algae reflect processes driving expansion of noncoding DNA and proliferation of introns - Sonja I. Repetti; Christopher J. Jackson; Louise M. Judd; Ryan R. Wick; Kathryn E. Holt; Heroen Verbruggen (PeerJ, 2020)
Within the siphonous green algal order Bryopsidales, the size and gene arrangement of chloroplast genomes has been examined extensively, while mitochondrial genomes have been mostly overlooked. The recently published mitochondrial genome of Caulerpa lentillifera is large with expanded noncoding DNA, but it remains unclear if this is characteristic of the entire order. Our study aims to evaluate the evolutionary forces shaping organelle genome dynamics in the Bryopsidales based on the C. lentillifera and Ostreobium quekettii mitochondrial genomes. In this study, the mitochondrial genome of O. quekettii was characterised using a combination of long and short read sequencing, and bioinformatic tools for annotation and sequence analyses. We compared the mitochondrial and chloroplast genomes of O. quekettii and C. lentillifera to examine hypotheses related to genome evolution. The O. quekettii mitochondrial genome is the largest green algal mitochondrial genome sequenced (241,739 bp), considerably larger than its chloroplast genome. As with the mtDNA of C. lentillifera, most of this excess size is from the expansion of intergenic DNA and proliferation of introns. Inflated mitochondrial genomes in the Bryopsidales suggest effective population size, recombination and/or mutation rate, influenced by nuclear-encoded proteins, differ between the genomes of mitochondria and chloroplasts, reducing the strength of selection to influence evolution of their mitochondrial genomes.